2006
DOI: 10.2307/3401112
|View full text |Cite
|
Sign up to set email alerts
|

Children with Disabilities Playing Musical Instruments

Abstract: a r e t F i tz g sabilities Playing ents cCord and e ral d 7ach fall, the music teacher held a meeting for fourth-grade students who wanted to learn to play ani:imsrument and their parents. She explained what instrumental music involved: how to obtain an ins-rument, which books would be required, how the ensembles were scheduled, expectations -or participation in concerts, and so on.One year, Stephanie and her grandmother came to the meeting. Stephanie had always wanted to Dlay the violin. She was a shy, quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The interviewees' understandings reveal a discourse that emphasises the segregated nature of special music education. This specialisation discourse can also be seen in music education research, which presents a distinction between "abled" people and students with "special needs" or "special educational needs" (e.g., Adamek & Darrow, 2010;Lapka, 2006;McCord & Fitzgerald, 2006;Melago, 2014;Ockelford, 2012). The following accounts exemplify the connection between the concept of special music education and the curricular level of such exclusionary policies which call for specialised curricula or schools for those with special needs (for the definition of special education, see Vehmas, 2010).…”
Section: Specialisation Discourse: Special Music Education As An Exclusionary Practicementioning
confidence: 99%
“…The interviewees' understandings reveal a discourse that emphasises the segregated nature of special music education. This specialisation discourse can also be seen in music education research, which presents a distinction between "abled" people and students with "special needs" or "special educational needs" (e.g., Adamek & Darrow, 2010;Lapka, 2006;McCord & Fitzgerald, 2006;Melago, 2014;Ockelford, 2012). The following accounts exemplify the connection between the concept of special music education and the curricular level of such exclusionary policies which call for specialised curricula or schools for those with special needs (for the definition of special education, see Vehmas, 2010).…”
Section: Specialisation Discourse: Special Music Education As An Exclusionary Practicementioning
confidence: 99%
“…Previous authors’ suggestions and experiences could help music teachers accommodate children with visual impairments (e.g., Best, 1958; Coates, 2012), who are Deaf or hard of hearing (Hash, 2003), and develop inclusion strategies (e.g., Mixon, 2005; Zdzinski, 2001). Furthermore, available literature can assist music teachers understand legal issues (Crockett, 2017), individualized education plans (McCord & Fitzgerald, 2006), and available materials such as adaptive instruments and technology (e.g., Chadwick & Clark, 1980; Clark & Chadwick, 1980; Darrow, 2011; McCord & Fitzgerald, 2006). Recently published books devoted to accommodating students in music education are also valuable resources for instrumental music teachers (e.g., Adamek & Darrow, 2018; Hammel & Hourigan, 2017; Jellison, 2015; Sobol, 2017).…”
Section: Need For the Studymentioning
confidence: 99%
“…Included studies are shown in Table 5, along with the levels of evidence to which they were assigned. Bergonzi (1996) Expert Opinion VI Chadwick & Clark (1980) Expert Opinion VI de l'Etoile (1996) Expert Opinion VI Frisque, Niebur & Humphreys (1994) Descriptive IV Hash 2003Expert Opinion VI Hessler-Binder 2002Expert Opinion VI Hoffman 2011Descriptive IV Hourigan 2009Case Study V Hourigan & Hourigan 2009Expert Opinion VI McCord & Fitzgerald (2006) Expert Opinion VI Mixon (2005) Expert Opinion VI F. Case Study V K. Expert Opinion VI Pinta 2013Case Shelfo (2007) Descriptive IV Siligo (2005) Expert Opinion VI Van Camp 1989Pre-post comparison III Vance (2004) Expert Opinion VI…”
Section: Data Evaluationmentioning
confidence: 99%